The Statue of a Doctor Who Experimented on Enslaved Women still Stands in Alabama. But now There’s also a Monument to His Victims. - Matchan, Linda (Washington Post, 2021)
Michelle Browder’s “The Mothers of Gynecology” remembers Black women who endured surgeries without anesthesia, or consent.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice noir.e; _Nettoyé